Relationship Between Health Literacy and Emergengy Department Usage - Güney, Eda; Özkan, Seçil (Turkey Health Literacy Journal, 2020)
There are many different definitions that having similar contents of health literacy of increasing importance in the fields of public health in recent years. It is important to have sufficient knowledge on the etiology and development of health problem to be convinced and change life‐style and behaviors in health literacy. Health literacy is defined as “people’s knowledge, motivation and competences to access, understand, appraise and apply health information in order to make judgements and take decisions in every‐day life concerning health care, prevention and health promotion to maintain or improve quality of life during the life course”. In the epidemiological studies on health literacy, it is observed that low health literacy affects health behavior , health outcomes, health service use and health costs in a negative way. One of the department which is affected by low health literacy in a negative way is emergency department. What is essential in emergency service is to provide this service to the most urgent as soon as possible. Application of non emergency patients increases the intensity. In our country, the number of patients experienced in emergency departments is a national and local health problem. On the basis of this problem, both sociological (emergency concept perception in patients) and insufficiency of managerial and physical environment appear. In addition, unrealistic emergency applications increase this problem. It has been shown in the studies conducted on this subject that the emergency department applicants think about their own situations urgently, and that all the examinations can be performed in the same day and that the results can be obtained quickly.